2014
DOI: 10.1002/pros.22806
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation of prostate cancer in Black South Africans

Abstract: BackgroundCompared with White Americans, Black American men are at a significant increased risk of presenting with prostate cancer (PCa) and associated mortality, suggesting a link to African-ancestry. However, PCa status within Africa is largely unknown. We address the clinical presentation of PCa within Black South African men.MethodsOver 1,000 participants with or without PCa have enrolled in the Southern African Prostate Cancer Study (SAPCS). Using genome-wide profiling we establish a unique within Africa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
74
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 68 publications
(97 citation statements)
references
References 35 publications
(49 reference statements)
13
74
1
Order By: Relevance
“…Intriguingly, African ancestry is significantly associated with high‐grade (Gleason score ≥ 8) PCa, which questions the role of TMPRSS2‐ERG fusions in tumor development in African populations. Reporting a 2.1‐fold increase in high‐grade PCa presentation in Black South African men compared with African Americans, we sought to determine the frequency, composition, and clinicopathological association of acquired TMPRSS2‐ERG fusions within non‐American men of African ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Intriguingly, African ancestry is significantly associated with high‐grade (Gleason score ≥ 8) PCa, which questions the role of TMPRSS2‐ERG fusions in tumor development in African populations. Reporting a 2.1‐fold increase in high‐grade PCa presentation in Black South African men compared with African Americans, we sought to determine the frequency, composition, and clinicopathological association of acquired TMPRSS2‐ERG fusions within non‐American men of African ancestry.…”
Section: Introductionmentioning
confidence: 99%
“…Within Africa, a greater disease burden has been suggested (1,6). The Southern African Prostate Cancer Study (SAPCS) has shown that South African men present with a 2-fold increase in aggressive disease compared with age-adjusted African Americans (7).…”
Section: Introductionmentioning
confidence: 99%
“…The incidence and mortality of the disease is disproportionately high among African American (AA) men compared to other ethnicities in the United States (3). An interesting note is that the disease incidence appears to be lower among Black men in Africa, although this has been attributed to the lack of adequate and sufficient statistics from this region of the world (4). …”
Section: Introductionmentioning
confidence: 99%